Characterization, modeling and enhancement of novel hybrid salinity gradient driven electrokinetic energy conversion - Jiao, Yanmei (2015)
This thesis reports a study of recently proposed novel hybrid energy conversion technique using a combined principle of electrokinetic (EK) and forward osmosis (FO). The proposed FO-EK energy conversion technique has been demonstrated by using a stack system comprising two submodules, a FO submodule and an EK submodule. Under a salinity gradient, a suction force is created to induce a hydrodynamic flow in the FO submodule based on the principle of FO. Accordingly, electric energy, in forms of EK streaming potential and/or streaming current, is generated across a porous glass housed in the EK submodule. This proposed power generation technique converts the salinity gradient energy into the electric energy without need of external pressure input.